2022
DOI: 10.3389/fpsyg.2022.935875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, sex, and education on California Verbal Learning Test-II performance in a Chinese-speaking population

Abstract: The California Verbal Learning Test-Second Edition (CVLT-II), is a commonly used tool to assess episodic memory. This study analyzed learning and memory characteristics in a cognitively healthy Chinese population, as well as the effects of age, sex and education on CVLT-II factors. In total, 246 healthy people aged 20–80 years and 29 persons with multiple sclerosis (MS) were included in this study and completed the CVLT-II. Factors including total learning, learning strategy, serial position effects, short-del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…On the other hand, birth-assigned females outperformed birth-assigned males on the Perdue Pegboard (η 2 P = 0.049) and on California Verbal Learning Test (η 2 P = 0.020), also with effect sizes ranging between small to medium. Again, both results align with the medium Cohen’s d reported in the literature [ 35 , 183 , 184 ]. Therefore, fine motor skills, verbal memory and verbal learning also exhibit some sexual polymorphism.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, birth-assigned females outperformed birth-assigned males on the Perdue Pegboard (η 2 P = 0.049) and on California Verbal Learning Test (η 2 P = 0.020), also with effect sizes ranging between small to medium. Again, both results align with the medium Cohen’s d reported in the literature [ 35 , 183 , 184 ]. Therefore, fine motor skills, verbal memory and verbal learning also exhibit some sexual polymorphism.…”
Section: Discussionsupporting
confidence: 90%
“…On the other, birth-assigned females outperformed birth-assigned males on the Perdue Pegboard (η 2 P = 0.049) and on California Verbal Learning Test (η 2 P = 0.020), also with effect sizes ranging between small to medium. Again, both results align with the medium Cohen's d reported in the literature (20,120,121). Therefore, ne motor skills, verbal memory and verbal learning also exhibit some sexual polymorphism.…”
Section: Birth-assigned Sex and Sexually Polymorphic Cognitionsupporting
confidence: 89%
“…We administered the probable reasons below. First, several studies showed that the wordlist learning test was positively associated with education [ 54 , 55 ], and the words in AVLT are written language and lack context. It might be difficult for illiterates or participants with low education to understand and remember.…”
Section: Discussionmentioning
confidence: 99%